Piosenka o piosence według Jerzego Wasowskiego i Jeremiego Przybory - Wiśniewski, Jerzy (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
Among numerous songs written by Wasowski and Przybora for the tv and radio show Old Gentlemen´s Cabaret two: Piosenka jest dobra na wszystko (A Song is a Universal Remedy) from the Fifth Evening of the Cabaret (14 May 1960) and Mambo Spinoza from the Eighth Evening (4 November 1961) might be considered autothematic. They represent an idea of ‘a song about a song’ — a common theme or motif in Polish popular music. In reaction to ideological degeneration of different forms of mass entertainment between 1949 and 1955 (the period known as Stalinism), Wasowski and Przybora decided to ‘redefine’ a song, writing these two pieces full of humour and allusions.